M2 -2mn + n2 =
4 - (-16) + 16 =
20 + 16 = 36
Have a nice days.......
Answer:
68%
Step-by-step explanation:
Calculate percentage change
from V1 = 82 to V2 = 138
(V2−V1)|V1|×100
=(138−82)|82|×100
=5682×100
=0.682927×100
=68.2927%change
=68.2927%increase
=68%
<h2>$86282.7</h2>
<em>Step-by-step explanation:</em>
<h3><em>p</em><em>r</em><em>i</em><em>n</em><em>c</em><em>i</em><em>p</em><em>l</em><em>e</em><em> </em><em>(</em><em>p</em><em>)</em><em> </em><em>=</em><em> </em><em>$</em><em>2</em><em>0</em><em>5</em><em>,</em><em>4</em><em>3</em><em>5</em></h3><h3><em>r</em><em>a</em><em>t</em><em>e</em><em> </em><em>(</em><em>r</em><em>)</em><em> </em><em>=</em><em> </em><em>2</em><em>.</em><em>8</em><em>%</em></h3><h3><em>t</em><em>i</em><em>m</em><em>e</em><em> </em><em>(</em><em>t</em><em>)</em><em> </em><em>=</em><em> </em><em>1</em><em>5</em><em> </em><em>y</em><em>e</em><em>a</em><em>r</em><em>s</em></h3><h3><em>s</em><em>i</em><em>m</em><em>p</em><em>l</em><em>e</em><em> </em><em>i</em><em>n</em><em>t</em><em>e</em><em>r</em><em>e</em><em>s</em><em>t</em><em> </em><em>=</em><em> </em><em>(</em><em>p</em><em> </em><em>×</em><em> </em><em>r</em><em> </em><em>×</em><em> </em><em>t</em><em>)</em><em> </em><em>÷</em><em> </em><em>1</em><em>0</em><em>0</em></h3><h3><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>=</em><em> </em><em>(</em><em>2</em><em>0</em><em>5</em><em>,</em><em>4</em><em>3</em><em>5</em><em> </em><em>×</em><em> </em><em>2</em><em>.</em><em>8</em><em> </em><em>×</em><em> </em><em>1</em><em>5</em><em>)</em><em> </em><em>÷</em><em> </em><em>1</em><em>0</em><em>0</em></h3><h3><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>=</em><em> </em><em>8,628,270</em><em> </em><em>÷</em><em> </em><em>1</em><em>0</em><em>0</em></h3><h3><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>=</em><em> </em><em>8</em><em>6</em><em>2</em><em>8</em><em>2</em><em>.</em><em>7</em></h3>
<h2>MARK ME AS BRAINLIST</h2><h2>PLZ FOLLOW ME</h2>
Answer: equality of a equation